Morpho-molecular identification and pathogenicity test on fungal parasites of guava root-knot nematode eggs in Lampung, Indonesia - I Gede Swibawa I Gede; YUYUN FITRIANA; SOLIKHIN; RADIX SUHARJO; F.X. SUSILO; EKA RANI; MEI SRI HARYANI; RACHMANSYAH A. WARDANA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Swibawa IG, Fitriana Y, Solikhin, Suharjo R, Susilo FX, Rani E, Haryani MS, Wardana RA. 2020. Morpho-molecular identification and pathogenicity test on fungal parasites of guava root-knot nematode eggs in Lampung, Indonesia. Biodiversitas 21: 1108-1115. This study aimed to obtain and discover the identity of the species of fungal egg parasites of root-knot nematodes (RKN), which have a high pathogenic ability causing major losses in vegetable crops. The exploration of the fungi was carried out in 2016 and 2018 from Crystal guava plantations in East Lampung, Central Lampung, Tanggamus, and NirAma, a commercial product that has been used for controlling Meloidogyne sp. in Indonesia. Identification was carried out based on morphological characteristics and molecular-based gene sequential analysis of Intergenic Transcribed Spacer (ITS) 1 and ITS 4. A pathogenicity test was carried out in vitro and in a greenhouse using tomato plants as indicator plants. In the in vitro test, observations were made on the percentage of infected RKN eggs. The observations in the greenhouse test were carried out on RKN populations in the soil and roots of tomato plants, root damage (root knots), and damage intensity due to RKN infection. The exploration resulted in five isolates of fungal egg parasites of RKN from the guava plantations in East Lampung (2), Central Lampung (1), Tanggamus (1), and from the isolation results of commercial products (1). The isolates were given codes as B4120X (PT GGP PG1), B3010 (PT GGP PG4), B412G (PT GGP PG 4), B01TG (Tanggamus), and BioP (Commercial products). Based on their morphological characteristics, the isolates were classified into the genus of Paecilomyces. The results of molecular identification showed that the discovered fungi were Purpureocillium lilacinum (Thom.) Luangsa Ard. (Syn. Paecilomyces lilacinus (Thom.) Samson.). Based on the in vitro tests, the five fungal isolates were able to parasitize RKN eggs at 86.4-100%. In the greenhouse test, all isolates significantly suppressed nematode populations in the soil and tomato roots, inhibited the formation of root knots, and produced lower damage intensity compared to controls. Among all the isolates tested, B01TG had the best ability to infect nematode eggs (99.5%), suppressing the formation of root knots, nematode population in the soil and the roots of tomato plants, and the damage intensity compared to other isolates.